Transition from ultrafast laser photo-electron emission to space-charge-limited current in a 1D gap - Liu, Yangjie (2014)
A one-dimensional (1D) model has been constructed to study the transition of the time-dependent ultrafast laser photo-electron emission from a flat metallic surface to the space-charge-limited (SCL) current, including the effect of non-equilibrium laser heating on metals at the ultrafast time scale. At high laser field, it is found that the space charge (SC) effect cannot be ignored and the SCL current emission is reached at a lower value predicted by a short-pulse SCL current model that has assumed a time-independent emission process. The threshold of the laser field to reach the SCL regime is determined over a wide range of operating parameters. The calculated results agree well with particle-in-cell simulation results. It is found that the SC effect is more important for materials with lower work function like tungsten (4.4 eV) as compared with gold (5.4 eV). However, for a flat surface, both materials will reach the SC limited regime at sufficient high laser field such as >5 GV m−1 with a laser pulse length of 10 s to 100 fs.